A new multiferroic ternary solid solution system: NdFeO3–Pb(Fe1/2Nb1/2)O3–PbTiO3. Issue 8 (June 2016) - Pang, Dongfang; He, Chao; Li, Xiuzhi; Han, Shujuan; Pan, Shilie; Long, Xifa
Abstract: Ceramic materials were sintered from powders of the NdFeO3 –Pb(Fe1/2 Nb1/2 )O3 –PbTiO3 (NF–PFN–PT) ternary system synthesized by the conventional solid reaction method and their multiferroic properties investigated. The structure, electric and magnetic properties of the ternary system have been investigated. The introduction of Pb(Fe1/2 Nb1/2 )O3 into the NdFeO3 –PbTiO3 binary system can effectively increase its electric properties. The ternary system exhibits enhanced piezoelectric property with optimal piezoelectric constants d 33 =143 pC/N, reduced coercive fields E C =5.78 kV/cm and remnant polarization P r =12.8 μC/cm 2 for 0.10NF–0.56PFN–0.34PT, near tetragonal phase region. The Curie temperature ( T C ) of the NdFeO3 –Pb(Fe1/2 Nb1/2 )O3 –PbTiO3 ceramics varies in the range from 108.7 °C to 67.9 °C. The magnetic hysteresis loops show that the ternary system is paramagnetic originating from canting of paramagnetic sublattices in NF–PFN–PT, due to the rare earth ions Nd 3+ influencing on the exchange interaction between Fe 3+ ions at the octahedral sites.